Humedad y germinación de semillas de Hyeronima alchorneoides(Euphorbiaceae) - González J., Eugenio (Universidad de Costa Rica, 1992)
The effect of loss of moisture on the gennination of seeds of Hyeronima alchorneoides Fr. Allemao (Euphorbiaceae) was studied. Seeds were collected at La Selva Biological Station, Costa Rica (1O"26'N, 83°S9W), and stored in an air-conditioned roan, with a mean relative humidity of 61 %, and temperature of noc. The mojature content was determined every twelve hours and germinatioo tests performjed. Fresh seeds, with a moisture content oi 68 %" had a 43 %, gernination, which was not different (P>O.OI) when the moisture content was reduced 10 14 %,